2006
DOI: 10.1002/ppul.20467
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled drugs for the prevention and treatment of bronchopulmonary dysplasia

Abstract: Bronchopulmonary dysplasia (BPD) is one of the most common long-term complications and treatment challenges in preterm infants. Theoretically, inhaled corticosteroids may suppress pulmonary inflammation without causing systemic side-effects, while bronchodilators will improve airway resistance and thereby work of breathing. This article reviews current data on these drugs in BPD prevention or treatment. Trials published to date have not demonstrated that regular bronchodilator administration influences the inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 52 publications
1
17
0
3
Order By: Relevance
“…Inhaled steroids, for instance, may improve the rate of successful extubation in premature infants, but do not seem to affect the rate of bronchopulmonary dysplasia. 5 Inhaled bronchodilators improve airway resistance but do not reduce the incidence of bronchopulmonary dysplasia. 5,14 These disappointing clinical results may reflect either an intrinsic lack of efficacy of these medications or suboptimal delivery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Inhaled steroids, for instance, may improve the rate of successful extubation in premature infants, but do not seem to affect the rate of bronchopulmonary dysplasia. 5 Inhaled bronchodilators improve airway resistance but do not reduce the incidence of bronchopulmonary dysplasia. 5,14 These disappointing clinical results may reflect either an intrinsic lack of efficacy of these medications or suboptimal delivery.…”
Section: Discussionmentioning
confidence: 99%
“…5 Inhaled bronchodilators improve airway resistance but do not reduce the incidence of bronchopulmonary dysplasia. 5,14 These disappointing clinical results may reflect either an intrinsic lack of efficacy of these medications or suboptimal delivery. Thus, we suggest that in future neonatal aerosol studies, particularly studies on nasal CPAP, documentation of drug delivery should be included in the study design.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Альтернативой примене-ния системных стероидов при БЛД являются ингаляцион-ные глюкокортикостероиды (ИГКС). До настоящего вре-мени нет данных о том, что использование ИГКС у детей с формирующейся или сформированной БЛД снижает частоту развития заболевания, приводит к снижению частоты симптомов или улучшает исходы [45][46][47][48]. С одной стороны, получены доказательства, что длительное использование будесонида в виде суспензии (код АТХ: R03BA02) в качестве противовоспалительной контроли-рующей (базисной) терапии детям с БЛД приводит к лик-видации тахипноэ и одышки в покое, уменьшению частоты обострений БЛД и госпитализаций в связи с ними, умень-шает выраженность симптомов дыхательной недостаточ-ности, модифицирует течение заболевания в сторону снижения степени тяжести [49], а также снижает уровень ферментов протеолиза, активных в первом полугодии жизни у детей с БЛД [50].…”
Section: (2а)unclassified
“…Therefore, the potential benefits arising from their use should be weighted against the risks in each case [6]. b 2 -agonists were studied in the early 1980s for the prevention or early treatment of BPD in pre-term infants [7,8]. However, a Cochrane review demonstrated no significant effect on any major outcomes [9].…”
Section: Bronchodilators B 2 -Agonistsmentioning
confidence: 99%